Pemeliharaan Prasarana Pendidikan di SMP Negeri se-Kecamatan Pelepat Ilir Kabupaten Bungo - Muhammad Anis Mursito; Sulastri Sulastri; Syahril Syahril; Hanif Al Kadri (Universitas Negeri Padang, 2021)
Study is based on the results of the author's observations regarding the maintenance of educational infrastructure that has not been carried out properly in Junior High School Negeri in Pelepat Ilir District, Bungo Regency. This study aims to obtain information regarding the maintenance of educational infrastructure in State of Junior High Schools in Pelepat Ilir District, Bungo Regency in terms of: maintenance of educational infrastructure based on time measurement, maintenance of educational infrastructure based on age of goods, usefulness and condition of goods. This study is descriptive quantitative. The population of this study is 110 teachers in State Junior High Schools in Pelepat Ilir Subdistrict, Bungo Regency, who have the status of Civil Servants (PNS) and their working period is more than 5 years. The sampling technique was simple random sampling using Cohran's theory. The selected sample was 56 people. The data were collected using a Likert scale model questionnaire which has been tested for validity and reliability. Data were analyzed using the average formula. The results of this study indicate that the Maintenance of Educational Infrastructure at State of Junior High Schools in Pelepat Ilir Subdistrict, Bungo Regency, seen from the aspect of maintaining educational infrastructure based on time measurement is in the good category with an average score of 4.4, maintenance of educational infrastructure by age of goods is in the good category with a score on average 3.7, maintenance of educational infrastructure based on usability was in the very good category with an average score of 4.8, and maintenance of educational infrastructure based on the state of goods in the good category was in the good category with an average score of 4.5. This it can be concluded that the maintenance of educational infrastructure in SMP Negeri in Pelepat Ilir District, Bungo Regency in the good category with an average score of 4.3.